Alpha2B-Adrenergic Receptor Regulates Neutrophil Recruitment in MSU-Induced Peritoneal Inflammation - Duan, Lihua; Chen, Jie; Razavi, Michael; Wei, Yingying; Tao, Ying; Rao, Xiaoquan; Zhong, Jixin (Frontiers in Immunology, 2019)
Gout is one of the most common metabolic disorders in human. Previous studies have shown that the disease activity is closely associated with sympathetic nervous system. α2B-adrenergic receptor (α2BAR), a subtype of α2 adrenergic receptor, plays a critical role in many diseases. However, the role of α2BAR in the pathogenesis of gout remains unclear. Here, we assessed the role of α2BAR in the monosodium urate (MSU) crystals-induced peritonitis that mimics human gout by using the α2BAR-overexpressing mice (α2BAR-Tg). We found that the number of recruited neutrophils was significantly increased in the α2BAR-Tg mice after MSU treatment, when compared with wild type mice. In contrast, the number of macrophages was not changed. Importantly, there is no difference in the IL-1β levels and caspase-1 activity between wild type and α2BAR-Tg mice in the gout animal model. Notably, the enhanced neutrophil migration in α2BAR-Tg mice was dependent on the α2BAR overexpression in neutrophils, but not resulted from other tissues or cells with α2BAR overexpression. In conclusion, our data provide a direct evidence that α2BAR plays a critical role in neutrophil migration and MSU-induced inflammation.